A Suspicion of Potter Syndrome in G4P2A1 at 33 Weeks Gestation with Oligohydramnios and Severe Preeclampsia: A Case Report - Arafah, Muhammad Gumelar; Mose, Glen Marion; Gurnadi, Jeffry Iman (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Background: Potter syndrome is a rare case caused by oligohydramnios due to kidney failure in a fetus. Potter syndrome is characterized by pulmonary hypoplasia, skeletal malformation, and kidney abnormalities.Case presentation: A 45-year-old G4P2A1 at 33 weeks gestation with oligohydramnios and severe preeclampsia came to the maternal and perinatal Emergency Unit at the Cibabat Regional General Hospital, Cimahi, complaining of labor contractions and delivered a baby. A male baby of 33 weeks gestation with a birth weight of 1295 grams was delivered. The baby had severe respiratory distress at birth, requiring resuscitation. Multiple congenital anomalies, such as widely separated eyes with epicanthic folds, low-set ears, receding chin, broad nasal bridge, and polydactyly, were noted. After 6 hours of life, the baby died due to respiratory failure.Discussion: In this case, clinical manifestations of Potter’s facies and a history of oligohydramnios support the suspicion of Potter syndrome. An autopsy or further examination was not carried out, so the etiology in this case has not been obtained.Conclusion: There was a suspicion of Potter syndrome obtained from clinical manifestations and a history of oligohydramnios.Dugaan Sindrom Potter pada G4P2A1 Parturien 33 Minggu dengan Oligohidramnion dan Preeklamsia Berat: Sebuah Laporan KasusAbstrakLatar belakang: Sindrom Potter merupakan kasus langka yang disebabkan oleh kurangnya cairan ketuban akibat gangguan pada ginjal janin. Pada kasus potter syndrome dapat ditemukan hipoplasia pulmonal, malformasi tulang, dan kelainan ginjal.Presentasi kasus: Ibu 45 tahun dengan G4P2A1 usia kehamilan 33 minggu dengan oligohidramnion dan preeklamsia berat datang ke IGD Maternal dan Perinatal RSUD Cibabat Cimahi dengan keluhan kontraksi persalinan dan melahirkan spontan bracht pervaginam. Bayi laki-laki usia 33 minggu, berat badan 1295gram, lahir dengan mengalami distress pernafasan berat dan dilakukan resusitasi. Kelainan kongenital multiple didapatkan pada bayi, yaitu jarak mata lebih lebar, adanya lipatan kulit yang menutupi sudut mata, posisi telinga lebih rendah, dagu lebih kecil, pangkal hidung yang lebih lebar, dan polidaktili. Dilakukan terapi suportif, setelah enam jam bayi meninggal karena distress pernafasan.Diskusi: Pada kasus ini ditemukan manifestasi klinis potter facies dan riwayat oligohidramnion yang mendukung kecurigaan terhadap Sindrom Potter. Pada kasus tidak dilakukan pemeriksaan otopsi maupun pemeriksaan lanjutan sehingga etiologi pada kasus ini belum didapatkan.Kesimpulan: Pada kasus ini didapatkan kecurigaan Sindrom Potter yang didapat dari manifestasi klinis dan riwayat oligohidramnion.Kata kunci: Sindrom Potter, oligohidramnion